2PAKEP: Provably Secure and Efficient Two-Party Authenticated Key Exchange Protocol for Mobile Environment - Kisung Park (IEEE Access, 2018)
With the increasing use of mobile devices, a secure communication and key exchange become the significant security issues in mobile environments. However, because of open network environments, mobile user can be vulnerable to various attacks. Therefore, the numerous authentication and key exchange schemes have been proposed to provide the secure communication and key exchange. Recently, Qi and Chen proposed an efficient two-party authentication key exchange protocol for mobile environments in order to overcome the security weaknesses of the previous authentication and key exchange schemes. However, we demonstrate that Qi and Chen's scheme is vulnerable to various attacks such as impersonation, offline password guessing, password change, and privileged insider attacks. We also show that Qi and Chen's scheme does not provide anonymity, efficient password change mechanism, and secure mutual authentication. In this paper, to overcome the outlined abovementioned security vulnerabilities, we propose a secure and efficient two-party authentication key exchange protocol, called 2PAKEP, that hides user's real identity from an adversary using a secret parameter. 2PAKEP also withstands various attacks, guarantees anonymity, and provides efficient password change mechanism and secure mutual authentication. In addition, we prove that 2PAKEP provides the secure mutual authentication using the broadly accepted Burrows-Abadi-Needham logic and the session key security using the formal security analysis under the widely accepted real-or-random model. Moreover, the formal security verification using the popular simulated software tool, Automated Validation of Internet Security Protocols and Applications, on 2PAKEP shows that the replay and man-in-the-middle attacks are protected. In addition, we also analyze the performance and security and functionality properties of 2PAKEP and compare these with the related existing schemes. Overall, 2PAKEP provides better security and functionality features, and also the communication and computational overheads are comparable with the related schemes. Therefore, 2PAKEP is applicable to mobile environment efficiently.